(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The electoral victory of Lula Inácio da Silva in Brazil consolidates the affirmation of a new progressive wave in the Latin American region. However, left-wing governments will have to face serious constraints, between the need to find agreements with the more moderate parliamentary forces and the aggressiveness of the neo-conservative right, starting with Bolsonarism.